THE CARDINAL VIRTUES IN THE CHRISTIAN UNDERSTANDING AND SĀMĀNYA DHARMA IN THE MANUSMṚTI: A COMPARATIVE ETHICAL STUDY - Puliappallil, Kochuthresia (Asian Horizons, 2016)
The genesis of this study is linked to the statement that captured my attention that “every moral question can be reduced to the consideration of the virtues.” This statement from James F. Keenan, one of the influential contemporary catholic virtue ethicists, generated within me an interest to delve deeper into the study of virtue ethics. The work undertakes an in-depth analysis of the ethics of virtue, its contemporary relevance, and a comparative study of the Christian and Hindu understanding of virtue ethics and its practical implications for day-to-day life. This study commences by deepening the understanding of the cardinal virtues in the Greek and Christian tradition and dharma in the Manusmṛti, one of the famous sources of Hindu ethics. The focus of this study is a comparative analysis of the cardinal virtues in the Christian and Hindu ethics, to decipher the areas of convergence, to build workable bridges between religious outlooks in view of fostering human relationships to strengthen unity and peace. To realize it, this study spells out a few proposals to give proper virtuous education from the early stages of life.